Hemostatic effects induced by Thalassophryne nattereri fish venom: a model of endothelium-mediated blood flow impairment. - Lopes Ferreira, Mónica (2002)
Accidents by Thalassophryne nattereri fish venom are characterised by severe local symptoms and signs including pain of fast onset, oedema and necrosis with impaired muscle regeneration. These effects have been related to alterations in hemostatic mechanisms and cytolytic effects rather than to conventional inflammatory pathways. In this work we evaluated the effects induced by the venom on microcirculatory vessels, platelets and blood coagulation. Effects evoked by topical application of venom on cremaster muscle were visualised through intravital microscopy. Stasis was observed, concomitantly with the presence of thrombi in venules and focal transient constrictions in arterioles, all of which impaired the blood flow. Significant alterations on vessel walls took place few minutes after venom application, characterised by increment in thickness, probably by deposition of fibrin. Increase in vascular permeability was also observed in venules. Additionally, the action of the venom was locally restricted since no alteration on systemic blood coagulation was observed. Venom lacked a direct pro-coagulant activity, but exerted a strong cytolytic effect on platelets and endothelial cells in vitro. These data suggest that venom action on endothelium may contribute to blood stasis and to the formation of platelet and fibrin thrombi, with the consequent ischemia, contributing to the local effects of the venom.